PENGOLAHAN DAGING DAN TELUR ITIK AFKIR GUNA MENINGKATKAN KETERAMPILAN KELUARGA KELURAHAN BOJONGKERTA BOGOR SELATAN - Anggraeni, Anggraeni; Wahyuni , Dewi; Malik, Burhanudin (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2021)
Duck meat is a source of protein from poultry which can be used to meet human animal protein needs. This is because duck meat has good nutritional content like chicken meat. However, duck meat is less favorable than chicken meat. Utilization of rejected ducks (Cairina Moschata) is still very limited. Refined duck meat has a characteristic odor, namely off odor and a rough and tough texture, so it requires separate handling so that it can be used further. Utilization of male or rejected duck meat has not been widely developed in the wider community. Meat tenderness is influenced by connective tissue protein, the older the livestock, the amount of connective tissue is greater, causing the meat to become tough or tough. This condition causes the rejected livestock to have a low selling price. Processing of meat and eggs can improve organoleptic and increase the variety of processed forms, allowing the preparation to be available at all times and save time and effort before the food is ready to be served. Bojongkerta Village has potential in duck farming. Ownership of land for farmers is relatively broad and is supported by less dense community settlements. However, the potential of the area is not supported by adequate.